Breaking public key cryptosystems on tamper resistant devices in the presence of transient faults - BAO, Feng (Institutional Knowledge at Singapore Management University, 2005)
In this paper we present a method of attacking public-key cryptosystems (PKCs) on tamper resistant devices. The attack makes use of transient faults and seems applicable to many types of PKCs. In particular, we show how to attack the RSA, the E1Gamal signature scheme, the Schnorr signature scheme, and the DSA. We also present some possible methods to counter the attack.